P024 Serum IL-10 is the best inflammatory variable to explain anti-TNF trough levels in a cohort of patients with Crohn's disease. (16th January 2018) - Almenara, S; Gutiérrez, A; Sempere, L; Zapater, P; Cameo, J; González-Navajas, J; Francés, R
Abstract: Background: The response to anti-TNF therapies is highly variable and the quantification of serum free anti-TNF levels to optimise treatment is controversial. The objective was to identify genetic, inflammatory, clinical and analytical parameters related with trough levels of anti-TNF in blood of CD patients. Methods: CD patients on regular or intensified schedules of anti-TNF therapy with infliximab or adalimumab were included. Genes associated with inflammation and autophagy were genotyped. Serum cytokine levels and anti-TNF drugs were evaluated. The presence of circulating bacterial (bact)DNA in blood was determined. Results: 112 CD patients with anti-TNF (62 on infliximab and 50 on adalimumab) were included. Thirty patients had a CDAI>150 (20 on infliximab [66.7%] and 10 on adalimumab [33.3%, p = 0.14]). 14 patients on infliximab (22.5%) and 15 on adalimumab (30%) were receiving an intensified regimen ( p = 0.37). Five intensified patients (17.2%) and 12 on regular schedule (14.6%, p = 0.74) were on steroids. No differences were found in clinical characteristics according to intensified vs. non-intensified regimen, regardless of biological drug used. We did not find differences in anti-TNF trough levels between infliximab (5414.4 ± 2336.6 ng/ml) and adalimumab (5612.9 ± 2116.8 ng/ml, p = 0.64) either. Intensified patients showed similar trough levels of anti-TNF (5154.9 ± 2416.9 ng/ml) vs. patients on regular schedule (5624.6 ± 2167.9 ng/ml, p = 0.36), despite higher doses or shorter intervals of use. Intensified patients showed a higher rate of bactDNA (65.5% vs. 28.9%, p = 0.0005), a variant NOD2 genotype (82.8% vs. 61.4%, p = 0.03567), and lower IL10 (35.1 ± 23.7 pg/ml vs. 40.0 ± 22.3 pg/ml, p = 0.044), higher IL26 (78.3 ± 36.1 pg/ml vs. 35.3 ± 32.4 pg/ml, p < 0.0001) and higher TNF (86.4 ± 15.3 pg/ml vs. 66.1 ± 31.1 pg/ml, p < 0.0001). Common clinical/analytical parameters (CDAI, fecal calprotectin, CRP, albumin) were not significantly associated with anti-TNF levels in the univariate analysis controlled by weight, type of anti-TNF and regimen. IL10 was the best fitting variable associated with anti-TNF (Figure 1). A strong correlation was present between real and IL10-predicted anti-TNF trough levels ( R 2 = 0.77). The addition of IL12 and bactDNA slightly improved the IL10 prediction of trough anti-TNF levels ( R 2 = 0.85). Conclusions: IL10 in blood is a good-fitting parameter explaining anti-TNF trough levels in CD patients. Results presented herein support IL10 inclusion in future studies analysing variability of anti-TNF levels.